2021
DOI: 10.1016/j.isci.2021.102266
|View full text |Cite
|
Sign up to set email alerts
|

The sphingosine kinase 1 activator, K6PC-5, attenuates Ebola virus infection

Abstract: Summary Ebola virus (EBOV) is responsible for outbreaks with case fatality rates of up to 90% and for an epidemic in West Africa with more than ten thousand deaths. EBOV glycoprotein (EBOV-GP) is the only viral surface protein and is responsible for viral entry into cells. Here, by employing pseudotyped EBOV-GP viral particles, we uncover a critical role for sphingolipids in inhibiting viral entry. Sphingosine kinase 1 (SphK1) catalyzes the phosphorylation of sphingosine to sphingosine 1-phosphate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 44 publications
4
10
0
Order By: Relevance
“…Interestingly, another study showed that a SK1 activator, K6PC-5, inhibited EBOV GP-mediated entry (21). Therefore, taken with our current study, this suggests that interfering with S1P production, whether it be positively or negatively, leads to inefficient EBOV entry.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Interestingly, another study showed that a SK1 activator, K6PC-5, inhibited EBOV GP-mediated entry (21). Therefore, taken with our current study, this suggests that interfering with S1P production, whether it be positively or negatively, leads to inefficient EBOV entry.…”
Section: Discussionsupporting
confidence: 79%
“…Additionally, inhibitors of sphingosine kinase 1 (SK1) and sphingosine-1-phosphate G-protein coupled receptors (S1PR) were also identified, suggesting a role for the SK-S1PR axis in EBOV GP-mediated entry (18). Interestingly, Imre and colleagues reported that a sphingosine kinase 1 activator or the overexpression of SK1 reduced EBOV-GP mediated entry, further suggesting a role for SK1 in EBOV entry, although the mechanism remains to be elucidated (21).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the inhibition of sphingosine kinase by bovine viral diarrhea virus NS3 is crucial for efficient viral replication and cytopathogenesis [ 33 ], and that the SphK1 activator K6PC-5 can alleviate Ebola virus infections [ 34 ]. However, Seo et al found that SphK1 plays a positive role in WSN (H1N1) virus infection and can promote the susceptibility of cells to the virus [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A negative effect of elevated S1P concentrations induced by the SphK activator K6PC-5 has been observed for Ebolavirus infections. The effect was independent of S1P receptors and appears to be mediated intracellularly, affecting the viral entry process ( Imre et al, 2021 ). Thus, sphingosine kinases and intracellular S1P can have differential effects on virus replication depending on the virus and the target cell.…”
Section: Intracellular Sphingolipid Interactions During Viral Replicationmentioning
confidence: 99%